WRITING AND PUBLISHING A MAGAZINE - Kusumayanthi, Susie (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2019)
Students who write a piece of writing need a perfect tool to engage themselves to write even when they are not interested in writing at all. One of the perfect tools to engage the students in writing process is creating a magazine as it offers students to publish their writing. Publication, according to Lange (1992) is a great tool to engage students to write, involving even those who do not consider themselves to be writers. This paper explores the implementation of writing and publishing a magazine in a writing class in one of the universities in Bandung. The class applies project-based learning as its teaching method.